Gender Disparities in Land Rights a Myth or a Reality? Case studies of the situations in Kenya and Tanzania - Issaka, Sule Ayannor (Journal of Economic Analysis, 2023)
All things being equal, and in a truly democratic world, one will expect that the fact that women are the majority in almost every single community of the world should guarantee them at least equal control or ownership over resources and enjoy most of the rights and privileges in that particular community. But things seem not to be working that way as evidence from the literature shows that women are always relegated to the background when it comes to the issue of control or ownership over, and sometimes even access to property in most societies which include the right to own and use land. This undoubtedly has a consequence on the productive and overall development of such a community. In recent times, the issue of gender discrimination, disparities, and inequalities has attracted the attention of researchers over the past decade with enormous literature in this area. There are, however, few studies that provide a comparative analysis of the situation between two or more countries. This paper seeks to fill this void of knowledge based on a review of relevant literature on land rights with an emphasis on the situations in Kenya and Tanzania. The results have shown the prevalence of four types of land rights such as communal property rights, non or open-access property rights, state or crown property rights, and private property rights. The results have further indicated that the controversial land rights of Kenya have led to the reduction in the lands of certain groups of people, increasing land disputes, and also discriminating against women in their land rights. In the case of Tanzania, there were several cases of bias against women concerning the ownership of land, especially under the customary system of Tanzania...